Nine o'clock in the morning - Bennett, Dennis J. (Plainfield, N.J. Logos International, 1970)
Experiences of an Episcopal minister in the charismatic movement.
Keywords: Bennett, Dennis J., -- 1917-1991. Baptism in the Holy Spirit. Bennett, Dennis J., -- 1917-1991